PERENCANAAN KURIKULUM MERDEKA BELAJAR DALAM PENINGKATAN MUTU PEMBELAJARAN DI SEKOLAH DASAR - Bahtiar, Luski; Harapan, Edi; Nugroho, Heri Setiyo (Jurnal Manajemen Pendidikan, 2024)
This research aims: 1) To describe independent curriculum planning in improving the quality of learning at SD Negeri 1 Bumiarjo Makmur, Lempuing District, Ogan Komering Ilir Regency; 2) To describe the independent curriculum planning strategy in improving the quality of learning at SD Negeri 1 Bumiarjo Makmur, Lempuing District, Ogan Komering Ilir Regency; 3) Describe the obstacles experienced by SD Negeri 1 Bumiarjo Makmur, Lempuing District, Ogan Komering Ilir Regency in improving the quality of learning. This research is descriptive qualitative with SWOT analysis. Data collection techniques through interviews, observation and documentation. The research data sources were 8 principals and teachers. Data analysis techniques are data reduction, data presentation and data verification. The results of this research are: 1) Independent curriculum planning to improve the quality of learning at SD Negeri 1 Bumiarjo Makmur, Lempuing District, OKI Regency has been carried out well; 2) The strategy for implementing the independent curriculum in improving the quality of learning at SD Negeri 1 Bumiarjo Makmur, Lempuing District, OKI Regency has been implemented as expected; 3) The obstacles experienced by SD Negeri 1 Bumiarjo Makmur, Lempuing District, Ogan Komering Ilir Regency in improving the quality of learning can be overcome well.